The effect of post-tensioning force and different cable arrangements on the behavior of cable-stayed bridge. (October 2022) - Atmaca, Barbaros; Ghafoori, Rafiullah; Dede, Tayfun; Ateş, Şevket
Abstract: In this study, the effect of the Post Tensioning Force (PTF) applied to the stay-cables and different cable arrangements on the behavior of cable-stayed bridges were presented. In this context, Nissibi Cable-Stayed Bridge was selected as an application area. The finite element model (FEM) of the bridge was modeled by using SAP2000 program. Two different FEMs of the bridge with different cable arrangements, fan and modified fan type, were created using the SAP2000 program. The proper set of PTF computed with the help of the developed optimization process which works in conjunction with Jaya metaheuristic algorithm and Open Applicable Programming Interface (OAPI) properties of SAP2000 with codes, was created in MATLAB. In the computation of the PTFs, design constraints were the vertical displacement of the deck, horizontal displacements of the pylon and stresses occurring in the stay-cables. PTFs were computed in a way that would not violate specified design constraints. The analysis of the FEMs of the bridge was carried out under different load combinations including dead, PTF, vehicle, wind and earthquake loads. At the end of the study, the effects of both PTF and different cable arrangements on the structural behavior of the bridge were examined separately and the obtained results were presented.